2018
DOI: 10.1111/aji.12865
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis‐induced cell‐mediated and humoral immune response in women with unexplained infertility

Abstract: Past chlamydial infection does not play a major role in unexplained infertility. Women with unexplained infertility and positive immune response to C. trachomatis do not have reduced pregnancy rates, but time to spontaneous pregnancy is longer among C. trachomatis IgG sero-positive women than among sero-negative women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Concerning the four articles that denied the association between CT infection and female infertility, Rantsi et al 18 and Hoenderboom et al 25 do affirm, however, that a longer time to conceive spontaneously was observed in women previously infected. This may indicate that past CT infection reduced the number of ciliated mucosal cells, leading to functional tubal damage and impairing the potential for pregnancy, even if it did not cause tubal occlusion.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning the four articles that denied the association between CT infection and female infertility, Rantsi et al 18 and Hoenderboom et al 25 do affirm, however, that a longer time to conceive spontaneously was observed in women previously infected. This may indicate that past CT infection reduced the number of ciliated mucosal cells, leading to functional tubal damage and impairing the potential for pregnancy, even if it did not cause tubal occlusion.…”
Section: Discussionmentioning
confidence: 95%
“…For example, studies conducted by Rantsi et al . 18 19 showed that CT+ women had a longer natural pregnancy time than CT− women, and persistent CT infection led to tubal infertility in women. Tang et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has a strong toxic effect on the body. It can destroy the structure of biological macromolecules such as nucleic acid and protein [19]. It is an important physiological index of oxidative stress and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%